Wideband Four-Way Filtering Power Divider With Sharp Selectivity and High Isolation Using Coshared Multi-Mode Resonators - Zhang, Gang; Qian, Zhenyao; Yang, Jiquan; Hong, Jia-Sheng (IEEE microwave and wireless components letters, 2019)
This letter presents an alternative fusion-design of a wideband four-way filtering power divider (FPD). A coshared coupling topology is proposed by embedding one pair of multi-mode resonators (MMRs) and three isolated resistors, bringing out wide power division band, decent frequency selectivity, and high in-band isolation. In comparison with other reported ones, the presented four-way FPD stands out not only by its favorable operation performance but also flexible topology that can also be easily extended to other multi-way multi-mode FPD designs and competitive size with a reduced number of resonators. A prototype is implemented to validate the design concept and method. Simulated results coincide well with the measured ones, verifying the theoretical design equations.